Multimetal Resistant, Alkalitolerant Bacteria Isolated from Serpentinizing Fluid-Associated Sediments and Acid Mine Drainage in the Zambales Ophiolite, the Philippines. Issue 9 (21st October 2019) - Vallalar, Bharathi; Meyer-Dombard, D'Arcy R.; Cardace, Dawn; Arcilla, Carlo A.
Abstract: Weathering in ophiolitic exposure settings often produces fluids and sediments that have elevated concentrations of various toxic heavy metals such as chromium, nickel, cobalt, copper, and zinc. Microorganisms inhabiting these environments (e.g., serpentinite soils or sediments) are likely adapted to tolerate these metals along with other physicochemical extremes. The purpose of this study is to isolate bacteria capable of tolerating extremely high concentrations of multiple metals and to assess the various tolerance mechanisms exhibited by different organisms. Sediment samples for microbial culturing were collected from Manleluag Spring National Park and Barlo Mine located on the island of Luzon, the Philippines. Luria-Bertani (LB) agar medium was supplemented with increasing concentrations of five trace elements – Cu, Cr, Co, Ni, and Zn. Over 20 isolates were obtained from media with concentrations ranging from 25 mg/L to 400 mg/L of each metal. Most isolates were identified as belonging to the genus Bacillus . Adaptation mechanisms, including potential biomineralization, were considered for select strains using inductively coupled plasma optical emission spectroscopy (ICP-OES), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray diffraction (XRD). ICP-OES analysis suggests that the primary resistance mechanism used by most isolates is cellular efflux, although it was determined that some organisms were able to reduce aqueous Cu concentration by up to 40%. Most strains exhibited growth at pH 12, demonstrating that alkalitolerant, highly metal resistant organisms are found in these ophiolite-associated environments. These organisms may be exploited for bioremediation, secondary metabolite production, and other industrial applications.